Does Diversification Affect Banking Systemic Risk? - Shouwei Li (Discrete Dynamics in Nature and Society)
This paper contributes to the understanding of the linear and nonlinear causal linkage from diversification to banking systemic risk. Employing data from China, within both linear and nonlinear causality frameworks, we find that diversification does not embody significant predictive power with respect to banking systemic risk.